2011
DOI: 10.1590/s0103-84782011005000041
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability of tropical maize cultivars in organic and conventional production systems

Abstract: The objectives were to identify maize germplasm for the organic productions system and to compare the genetic effects of the grain yield of maize cultivars in organic and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
4
0
2
Order By: Relevance
“…This scenario of low variation, considering the yield potential of the crop, is a direct reflection of the low estimate of the variance component related to GCA in comparison to SCA. Oliveira et al (2011) observed that low variance estimates of GCA were also reflected in low amplitude in the estimates of GCA of the progenies, just as observed in this study. Balestre et al (2010) found that the variances of the BLUP values of the combining abilities (GCA and SCA), estimated from 90 S 0:2 progenies genotyped with 25 microsatellite markers, were low, corroborating the results obtained in this study.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This scenario of low variation, considering the yield potential of the crop, is a direct reflection of the low estimate of the variance component related to GCA in comparison to SCA. Oliveira et al (2011) observed that low variance estimates of GCA were also reflected in low amplitude in the estimates of GCA of the progenies, just as observed in this study. Balestre et al (2010) found that the variances of the BLUP values of the combining abilities (GCA and SCA), estimated from 90 S 0:2 progenies genotyped with 25 microsatellite markers, were low, corroborating the results obtained in this study.…”
Section: Resultssupporting
confidence: 87%
“…In contrast, Englesong et al (2011), Oliveira et al (2011), Paterniani et al (2006, and Rovaris et al (2014) studies higher estimate of GCA in relation to SCA indicated that additive gene action contributes more toward an increase in yield. Such divergent results can be explained by the simple fact that combining ability of a genotype is relative to other genotypes being tested; thus, a determined genotype can exhibit high or low GCA, depending on genotypes that are being tested.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…O efeito do cultivo orgânico sobre o tamanho das espigas pode ser devido a falta de nutrientes prontamente disponíveis nesse sistema, pois Freire et al (2010) . Segundo Oliveira et al (2011) as diferenças na performance de cultivares de milho são comuns em regiões tropicais e sistemas de produção com baixa ou alta entrada de insumos.…”
Section: Tratamentosunclassified
“…The behavior of each genotype varies between regions, which can be capitalized upon to maximize productivity (Fritsche-Neto et al, 2010a;Faluba et al, 2010). Local food security can be increased via the identification of genotypes with improved performance in specific environments such as organic production systems (Oliveira et al, 2011) and soils with low N availability Li et al, 2011), low P availability (Fritsche-Neto et al, 2010b;George et al, 2011), and high salinity (Ferreira et al, 2007).…”
mentioning
confidence: 99%